Semitauonic B decay anomaly - Fortes, E. C.F.S. [UNESP]; Nussinov, Shmuel (American Physical Society (APS), 2016)
The anomalously large experimentally measured ratios of the semitauonic decay B→D(∗)+τ+ν and the corresponding semileptonic B→D∗+l+ν¯l disagree with the predictions of the standard E.W+QCD model (SM). We briefly comment on this disagreement and on possible new physics explanations which are rather constrained and difficult to implement.